Beyond the classical amyloid hypothesis in Alzheimer's disease: Molecular insights into current concepts of pathogenesis, therapeutic targets, and study models. Issue 2 (9th December 2022) - Theerasri, Atsadang; Janpaijit, Sakawrat; Tencomnao, Tewin; Prasansuklab, Anchalee
Abstract: Alzheimer's disease (AD) is one of the progressive neurodegenerative disorders and the most common cause of dementia in the elderly worldwide causing difficulties in the daily life of the patient. AD is characterized by the aberrant accumulation of β‐amyloid plaques and tau protein‐containing neurofibrillary tangles (NFTs) in the brain giving rise to neuroinflammation, oxidative stress, synaptic failure, and eventual neuronal cell death. The total cost of care in AD treatment and related health care activities is enormous and pharmaceutical drugs approved by Food and Drug Administration have not manifested sufficient efficacy in protection and therapy. In recent years, there are growing studies that contribute a fundamental understanding to AD pathogenesis, AD‐associated risk factors, and pharmacological intervention. However, greater molecular process‐oriented research in company with suitable experimental models is still of the essence to enhance the prospects for AD therapy and cell lines as a disease model are still the major part of this milestone. In this review, we provide an insight into molecular mechanisms, particularly the recent concept in gut‐brain axis, vascular dysfunction and autophagy, and current models used in the study of AD. Here, we emphasized the importance of therapeutic strategy targeting multiple mechanisms together with utilizing appropriate models for the discovery of novel effective AD therapy. This article is categorized under: Neurological Diseases > Molecular and Cellular Physiology Abstract : Current understanding of mechanisms underlying AD pathogenesis and some common non‐rodent study models (Created with BioRender.com ).